Rutinas y criterios para la elaboración y la edición de la portada del diario El Comercio - Bazán Coquis, Luis Adolfo (2020)
This sufficiency report supports the professional experience in planning and preparing the cover of the newspaper El Comercio, in the editions from Monday to Friday, in the period between 2007 and 2020. Since its foundation in 1839, the first page of the Dean of the National Press has undergone innumerable changes, according to the demands of time and its audiences. From the experience of the author of this professional report, it is considered that the process of preparing a cover requires certain work routines, as well as the application of criteria and evaluations that the editor must follow to determine which is the most relevant information. The report describes this process through the analysis of some covers edited personally by Adolfo Bazán Coquis, in which events of historical relevance were highlighted. They are also compared with those published in other national newspapers. The professional experience presented shows a little explored area of journalistic work and about which there is no profuse documentation. It is an academic approach that by its very nature can be described, if not as unprecedented, then as valuable due to its novel nature.